Penafsiran Ayat Berkaitan dengan Bullying dalam Al-Quran - Rafka Bulan Nafisa; Hafidh Satria; Ahmad Sukri Alamsyah Ginting; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The interpretation of verses in the Qur'an related to bullying is an important study in the social and religious context. Bullying has become a global issue that negatively affects individuals' mental and emotional health, especially children and teenagers. In the Qur'an, there are several verses that teach the importance of mutual respect, protecting others' feelings, and avoiding actions that harm or degrade others. This study aims to explore and interpret verses related to bullying behaviors and explain the Islamic principles that encourage mutual respect and compassion among people. Through a contextual tafsir approach, this article attempts to link the universal values in the Qur'an to the phenomenon of bullying in modern society, hoping to provide a deeper understanding of how Islam views mistreatment of others.